PEMBAHARUAN KONTRAK ANTARA LEMBAGA JASA KEUANGAN DENGAN KONSUMENNYA PASCA BERLAKUNYA PERATURAN OTORITAS JASA KEUANGAN NOMOR 01/POJK.07/2014 - Ema Rahmawati; Aam Suryamah (Jurnal Ilmiah Hukum DE'JURE: Kajian Ilmiah Hukum, 2019)
Based on the concept of regulation, dispute resolution in the financial services sector arising from consumer complaints must first be resolved internally at the relevant financial service institution which is more concerned with negotiation or deliberation settlement to reach consensus. Furthermore, if no complaint resolution agreement is reached, consumers and financial service institutions can resolve disputes, by way of resolution through LAPS in their respective financial services sectors or through the courts. The writing of this article is basically a research result that uses normative juridical research methods, namely legal research on the principles of law, the rule of law and the comparison of law with the method of analytical descriptive approach. The results of the study, the legal consequences of the implementation of the LAPS POJK include the need for an agreement (clause) for the selection of a dispute resolution mechanism, either an arbitration forum or other alternative dispute resolution in the event of a dispute or dispute in accordance with the LAPS POJK. Renewal of these contracts is ideal for supporting legal protection for consumers and financial service institutions and supporting renewal of contract law in Indonesia.